The effect of macroeconomic variable towards portfolio investment in Malaysia/ Sharmine Nadia Suleiman - Suleiman, Sharmine Nadia (2018)
There is still lacking of research on performance portfolio investment. This is because major studies was focus on the stock market volatility like (Menike, 2010)(Cooper, Lee, Howe, & Hamzah, 2004)(Murthy, Anthony, & Vighnesvaran, 2016) and (Muhammad Akbar, 2012). Most of their studies on stock market volatility. Thus, Portfolio investment is an investment in the form of the group (portfolio) of assets including transaction of equity securities, such as common stock and debt securities, such as banknotes, bond and debentures. It also can be known as passive investment of securities in portfolio. When we talk about portfolio it deals with the asset allocation and diversification to construct a collection of investment. Unfortunately, it will deal the challenges in investing in order to predict in the future performance and thus the risk of potential investment losses. Portfolio investment will be important in terms of diversify the company investment, because of prevent from investing all of money in a single company. It also always spread investments across a number of companies and considers investing in companies that operate in different market sectors. Other than that, portfolio management is a perfect way to select the best investment strategy based on age, income, risk taking the capacity of the individual and investment budget. This research aim is to study the effect of macroeconomic variable towards portfolio investment in Malaysia. It specifically studies on performance portfolio investment in Malaysia from 1981 until 2016. This research is based on data obtained from Data Stream and Data World bank. The result of studies suggest Malaysia has successful manage their net portfolio investment in Malaysia rather than other countries.